Slippery characters : ethnic impersonators and American identities - Browder, Laura, 1963- (Cultural studies of the United States., 2000)
This work examines the tradition of ethnic impersonators in the United States. It looks at works such as Welsh Baptist Elizabeth Stern's immigrant narrative "I am a Woman - and a Jew", and uncovers their surprising influence on American notions of identity